Aliança como fator de vantagem competitiva sustentável: um estudo exploratório no setor varejista farmacêutico - Ribeiro, Bianca Bonassi (2006)
The present study is a exploratory research which refers to the possibility of pharmacies and drugstores establish a partnership in order to reach sustainable competitive advantage within the region of Bragança Paulista, São Paulo s countryside. Brazil is the 8th country in the medication market where 80% of the businesses correspond to the medication´ selling, according to the study accomplished by the BNDES Sectorial Management of Commerce and Services. Nowadays, there are about 56.000 pharmacies and drugstores which fit in one of the following structures: a) independents; b) groups; c) co-operatives; and d) franchises. The theoretical reference follows explaining the context, the concept, the development and the sustainable competitive advantage. To this part of the research, the theoretical investigation was based on Ansoff (1977), Porter (1986), Mintzberg (1994), Ohmae (1998), Hill and Jones (1998), Aaker (2001), Barney (2002) and Grant (2002). The theoretical reference also presents the partnership strategy as an alternative to obtain the competitive advantage. To defend this idea the following theorists were consulted: Hill and Jones (1998), Inkpen (2001), Thompson and Strickland (2001) and Barney (2002). The research problem that guided this study was to identify the relation between the strategic partnership and the sustainable competitive advantage in pharmacies and drugstores. A quality fieldwork was conducted with ten pharmacies and drugstores managers in the cities of Bragança Paulista and Atibaia. The main purpose was to verify, through the retailers opinion, if there is a sustainable competitive advantage in forming strategic partnerships. The collected data was interpreted by the contents analysis developed by Bardin (1977). It was verified that the researched pharmacies and drugstores used seven types of strategic partnerships (franchises, co-operatives, exclusive supplier, own covenants, outsourced covenants, partnerships between manipulation pharmacies and drugstores and, at last, partnerships with other pharmacies and drugstores to share the purchase). When comparing the fieldwork collected data to the researched theoretical reference in the present study, it concludes that partnerships promote competitive advantage to the pharmaceutical retail studied.